Strategi Komunikasi Interpersonal antara Atasan dan Bawahan dalam Meningkatkan Kinerja Karyawan PT. Adyawinsa Telecommunications & Electrical - Anisti; Mutiah, Tuty; Raihaanah Hisaanah, Naurah (Journal of Multidisciplinary Inquiry in Science, Technology and Educational Research, 2024)
The move of the Energy Solutions division to Constructions and the change in leadership in January 2024 emphasize the importance of the new leadership's interpersonal communication. This research explores effective leadership communication strategies to improve employee performance throughout the company. To understand interpersonal communication strategies between leaders and subordinates at PT. Adyawinsa Telecommunication & Electrical, this research uses the case study method. A qualitative approach allows collecting data from various sources, including observations, interviews, and documents. The case study approach also allows for the collection of data from various other sources. At PT. Adyawinsa Telecommunications & Electrical, construction division, interpersonal communication between leaders and subordinates is very important. Openness, positive attitudes, empathy, support and equality are the basis of communication strategies. This approach encourages collaboration, motivation and innovation, improves employee performance and team synergy, and strengthens the company's strategic achievements. Research in the Constructions Division of PT. Adyawinsa Telecommunications & Electrical shows that interpersonal communication between leaders and subordinates increases employee productivity, performance, motivation and engagement.